2015
DOI: 10.1016/j.archoralbio.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint fibrocartilage degeneration from unilateral dental splints

Abstract: Objective The objective of this study was to determine the extent to which altered loading in the temporomandibular joint (TMJ), as might be associated with a maloclussion, drives degeneration of articulating surfaces in the TMJ. We therefore sought to quantify the effects of altered joint loading on the mechanical properties and biochemical content and distribution of TMJ fibrocartilage in the rabbit. Design Altered TMJ loading was induced with a 1 mm splint placed unilaterally over the maxillary and mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Changes in the ratio of type I/III collagen impact the material properties of the extracellular matrix [ 47 ]. This may explain why overloaded MCC is associated with a low compliance, high stiffness matrix [ 48 ]. In silico modeling predicts that the superficial layer promotes interstitial fluid pressurization during loading, lowering the deformation of the cartilage, and lowering the frictional forces on the condyle [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the ratio of type I/III collagen impact the material properties of the extracellular matrix [ 47 ]. This may explain why overloaded MCC is associated with a low compliance, high stiffness matrix [ 48 ]. In silico modeling predicts that the superficial layer promotes interstitial fluid pressurization during loading, lowering the deformation of the cartilage, and lowering the frictional forces on the condyle [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The persistent change in kinematics likely resulted from the abnormal occlusion and degeneration of the condylar fibrocartilage observed in our previous studies. 7,19 The kinematics of the rabbit TMJ at the condyles and the incisors were easily measured using our noninvasive system before and after splint placement to determine the changes in the joint movement. The decreased range in incisal movement after splinting was comparable to a previous TMJ disc injury study.…”
Section: Discussionmentioning
confidence: 99%
“…The altered occlusion model used in the present study has been shown to produce condylar fibrocartilage degeneration that would likely not be detected using conventional magnetic resonance imaging. 7,19 Understanding the changes in joint movement that occur from various types of TMJDs could allow for earlier diagnosis and treatment; for example, if a certain signature of changes in movement are observed earlier before the onset of severe joint degeneration. As such, our findings suggest that decreases in 20% anteroposterior displacement of the working condyle might be indicative of condylar degeneration and early-stage TMJ-OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbit is a larger animal, and provides large enough tissues for reliable mechanical testing such as compression, tensile, shear, and friction. 24 It is important to note that the altered loading models are designed to understand the impact of a large change in the distribution of loads. These models do not replicate clenching or bruxism, but give insight into the mechanisms by which these behaviors could give rise to degeneration of the joint.…”
Section: Mechanical Methodsmentioning
confidence: 99%